Bubbler: A Novel Ultra-High Power Density Energy Harvesting Method Based on Reverse Electrowetting - Hsu, Tsung-Hsing; Manakasettharn, Supone; Taylor, J. Ashley; Krupenkin, Tom (Scientific reports, 2015)
We have proposed and successfully demonstrated a novel approach to direct conversion of mechanical energy into electrical energy using microfluidics. The method combines previously demonstrated reverse electrowetting on dielectric (REWOD) phenomenon with the fast self-oscillating process of bubble growth and collapse. Fast bubble dynamics, used in conjunction with REWOD, provides a possibility to increase the generated power density by over an order of magnitude, as compared to the REWOD alone. This energy conversion approach is particularly well suited for energy harvesting applications and can enable effective coupling to a broad array of mechanical systems including such ubiquitous but difficult to utilize low-frequency energy sources as human and machine motion. The method can be scaled from a single micro cell with 10 −6 W output to power cell arrays with a total power output in excess of 10 W. This makes the fabrication of small light-weight energy harvesting devices capable of producing a wide range of power outputs feasible.